PENERAPAN MODEL PEMBELAJARAN BIOLOGI BERBASIS REMAP-STAD UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KOGNITIF MAHASISWA IKIP BUDI UTOMO MALANG - Pangestuti, Ardian Anjar (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2017)
The results of PISA, PIRLS and reports from other sources mentioned that Indonesian student achievement is not better when compared with the achievements of students from other countries. It can caused by learning proccesses in Indonesia is less empowering students’s reading skills. These conditions need to be changed because of the low literacy reading students will be able to have an impact on thinking skills and student learning outcomes. One attempt to solve this problem is to implement a model of learning in which there are reading, construct a concept map, and applying cooperative learning in classroom or it can called Remap Coople (Reading + Concept Mapping + Cooperative Learning). Cooperative learning that used in this research is Student Teams Achievement Divisions (STAD), so that this model is called Remap-STAD. This type of research is the Classroom Action Research (CAR). Subjects were students of class B and class 2016 General Biology course participants. The number of students in the classroom as much as 35 people. This study was conducted on 24 September – 24 December 2016. The results showed that the Remap-STAD can improve students's critical thinking skills in General Biology courses at Budi Utomo College. It is known from the results of the analysis of the final test cycle showed an increase in scores from the first cycle to the second cycle. The average score of critical thinking skills first cycle was 65.0, while in the second cycle is 72.2. The learning models can also improve cognitive achievement that is the first cycle of 56.4 rose to 69.4 in the second cycle.